DEVELOPING PROFESSIONAL DEVELOPMENT MODEL FOR PHYSICAL EDUCATION, SPORTS, AND HEALTH PRIMARY SCHOOL TEACHERS IN LEARNING ORGANIZING - Mu’arifin, Mu’arifin; Kurniawan, Ari Wibowo; Paulina, Febrita (Program Pascasarjana Universitas Negeri Jakarta, 2018)
This research aimed at developing and assessing the validity of professionalism coaching model for Physical Education, Sports, and Health (PESH) primary school teachers in conducting lesson. The development method was used to succeed the research. The created prototype models were in forms of three coaching device documents: coaching module, module administration guidance, monitoring guidance, and coaching evaluation. Upon passing expert review, usability test, and pilot assessment, this model had been attested valid, practical, and effective for further being applied as coaching model to build up the professionalims of PESH teachers in conducting lesson. Keywords: professional Development Model, PESH Teacher, Learning Organizing.